The Uncertainty of Hope - Tagwira, Valerie (Book collections on Project MUSE., 2007)
The Uncertainty of Hope by Valerie Tagwira, a novel which Charles Mungoshi calls 'an astonishing debut'. Through the various and complex lives of Onai Moyo - a market woman and responsible mother of three children, and her best friend Katy Nguni - a vendor and black-market currency dealer - we are given an insight into the challenges that face those who only survive by their wits, their labour and their mutual support. In doing so Tagwira aptly captures how precarious the future is for the inhabitants of Mbare, Zimbabwe in 2005. The story of these two close friends is situated in a high-densit.